2020
DOI: 10.1070/rcr4902
|View full text |Cite
|
Sign up to set email alerts
|

A.E.Favorskii’s scientific legacy in modern organic chemistry: prototropic acetylene – allene isomerization and the acetylene zipper reaction

Abstract: Alexei Evgrafovich Favorskii was an outstanding organic chemist who left a great scientific legacy as a result of long time and fruitful work. Most of the theoretically and practically important discoveries of A.E.Favorskii were made in the chemistry of acetylene and its derivatives. Nowadays, the reactions discovered by him, which include acetylene – allene isomerization, the Favorskii and retro-Favorskii reactions, the Favorskii rearrangement and the vinylation reaction, are widely used in industry and in la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 238 publications
0
6
0
Order By: Relevance
“…The effectiveness of this approach was shown previously in our research group [ 35 ]. At the first stage, 2,7-dimethylocta-3,5-diyne-2,7-diol 1 was subjected to retro-Favorskii reaction by the heating with K 2 CO 3 [ 36 , 37 ] to synthesize 2-methylhexa-3,5-diyn-2-ol 2, which was subjected to Sonogashira coupling with iodoarenes 3a – c [ 38 ]. Obtained compounds 4a – c were involved in retro-Favorskii reaction again using KOH.…”
Section: Resultsmentioning
confidence: 99%
“…The effectiveness of this approach was shown previously in our research group [ 35 ]. At the first stage, 2,7-dimethylocta-3,5-diyne-2,7-diol 1 was subjected to retro-Favorskii reaction by the heating with K 2 CO 3 [ 36 , 37 ] to synthesize 2-methylhexa-3,5-diyn-2-ol 2, which was subjected to Sonogashira coupling with iodoarenes 3a – c [ 38 ]. Obtained compounds 4a – c were involved in retro-Favorskii reaction again using KOH.…”
Section: Resultsmentioning
confidence: 99%
“…Disconcertedly, close inspection of the NMR spectra of product ( 27 ) revealed the presence of unexpected signals, not entirely supporting the structure. Although the HRMS obtained (467.2078 amu obtained, expected 467.2083 amu) supported the required molecular formula, examination of the NMR spectra indicated that what we had in hand was a compound in which the alkyne had isomerized into the thermodynamically favored internal position (see Scheme c for structure of actual compound 30 ) . Examination of compound 30 ’s 1 H NMR spectrum showed all the pyrrolo[2,3- d ]pyrimidine core signals, together with the morpholine methylene signals.…”
Section: Resultsmentioning
confidence: 83%
“…These two alterations effectively resulted in the internalization of the alkyne, a process which was further verified during the synthesis of analogue 31 . In retrospect, the distinctive proton signals supporting alkyne internalization suggests that the C7 para -morpholine sample 15 also contains a fraction (approximately 25% as determined from 1 H spectra integration) of its internal alkyne isomer . Notably, solubilization of pyrrole 12 required only a small volume of DMSO without further temperature increase, thereby resulting in alkyne internalization to a much lesser extent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tertiary propargyl alcohols capable of undergoing a base-mediated C–C bond cleavage (the retro-Favorskii reaction 33 ) are easy to store and inexpensive precursors of terminal alkynes. 34 Several groups evaluated these substrates in the tandem deacetonative Sonogashira coupling under Pd catalysis (Scheme 1C).…”
Section: Introductionmentioning
confidence: 99%